Application of probability filter for maintenance of air objects - Piskunov, S.; Iasechko, M.; Yukhno, O. O.; Юхно, О. О.; Polstiana, N.; Gnusov, Y. V.; Гнусов, Ю. В.; Bashynskyi, K.; Kozyr, A.; Олександр Юхно; Юрій Гнусов (International journal of computer science and network security. – 2021. – Vol. 21, No 5. – P. 31-34, 2021)
У статті розглядаються можливості підвищення точності оцінок параметрів траєкторії мети при забезпеченні заданої ймовірності сталої підтримки повітряного об'єкта, зокрема при його маневрі.

The article considers the possibilities of increasing the accuracy of estimates of the parameters of the trajectory of the target with the provision of a given probability of stable support of the air object, in particular, during its maneuver. The aim of the work is to develop a filtration algorithm that provides a given probability of stable tracking of the air object by determining the regular components of filtration errors, in particular, when maneuvering the air object, and their compensation with appropriate correction of filter parameters and estimates of air object trajectory parameters.

В статье рассматриваются возможности повышения точности оценок параметров траектории цели при обеспечении заданной вероятности устойчивой поддержки воздушного объекта, в частности, при его маневре.
Keywords: Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; air object tracking; filtering errors; air object; фільтр Калмана; відстеження повітряного об'єкта; помилки фільтрації; повітряний об'єкт; Kalman filter; фильтр Калмана; слежение за воздушным объектом; ошибки фильтрации; воздушный объект